Learning skills for distance learners : providing 21st century learning support - Kaur, Abtar, Prof Dr; Al-Oraini , Sara (2007)
One of the main goal of open and distance education (ODE) programmes is to ensure that knowledge and skills gained possitively affect performance or bahaviour. Apart from that, ODE programmes should also ensure learners extend their existing learning skills.